The Influence of TAPPS Technique and Students’ Attitude toward Students’ Reading Comprehension Achievement to the Eighth Grade Students of Air Satan Junior High School - Fahrudin Rizani (Universitas PGRI Palembang, 2015)
The aims of the research were to find whether or not (1) there was any significant difference in reading comprehension between the students who had positive attitude taught using TAPPS technique and conventional, (2) there was any significant difference in reading comprehension between the students who had positive attitude taught using conventional and negative attitude taught using TAPPS technique, (3) there was any significant different in reading comprehension between the students who had negative attitude taught using TAPPS technique and conventional, (4) there was any significant different in reading comprehension between the students who had negative attitude taught using conventional and positive attitude taught using TAPPS technique,(5) there was any significant interaction between TAPPS technique and reading attitude in increasing students’ reading comprehension. The population of this research was the eighth class of students SMP Negeri Air Satan in 2014-2015 academic years. From the population 90 students were taken as his research sample 30 students represent an experimental class and the 30 students as a control class. The samples were taken using two stage random sampling. In carrying out the research, the writer used factorial group design, the writer distributed the pretest, posttest, and questionnaire on students reading attitude (positive and negative) in collecting the data. In analyzing the data, t-test and two way ANOVA were used. There was any significant different on positive attitude students in experimental class and positive attitude students in control class. There was any significant difference on negative attitude students in experimental class and positive attitude students in control class. There was any significant different on negative attitude students in experimental class and negative attitude students in control class. There was any significant difference on positive attitude students in experimental class and negative attitude students in control class. The last, there was no any significant interaction between the students’ reading attitude and technique used. Key words: Influence, TAPPS technique, Reading Attitude, and Reading Comprehension.